CO2 Pneumoperitoneum Preserves β-Arrestin 2 Content and Reduces High Mobility Group Box-1 (HMGB-1) Expression in an Animal Model of Peritonitis. (24th February 2015) - Montalto, Angela Simona; Bitto, Alessandra; Minutoli, Letteria; Impellizzeri, Pietro; Costa, Gaetano; Irrera, Natasha; Pizzino, Gabriele; Squadrito, Francesco; Altavilla, Domenica; Romeo, Carmelo
Abstract : Laparoscopy (LS) has been shown to decrease the inflammatory sequelae of endotoxemia. β -arrestin 2 plays an important function in signal transduction pathway of TLR4. High mobility group box-1 (HMGB-1) is involved in the delayed systemic inflammatory response. We investigated the effects of CO2 insufflation on liver, lung, and kidney expression of both β -arrestin 2 and HMGB-1 during sepsis. Cecal ligation and puncture (CLP) was performed in male rats and 6 h later the animals were randomly assigned to receive a CO2 pneumoperitoneum or laparotomy. Animals were euthanized; liver, lung, and kidney were removed for the evaluation of β -arrestin 2 and HMGB-1 expression. Immunohistochemical detection of myeloperoxidase (MPO) was investigated in lung and liver and bacterial load was determined in the peritoneal fluid. CO2 pneumoperitoneum reduced peritoneal bacterial load, increased the expression of β -arrestin 2, and blunted the expression of the potent proinflammatory HMGB-1 in liver, lung, and kidney compared with laparotomy. Liver and lung MPO was markedly reduced in rats subjected to LS compared with laparotomy. We believe that CO2 exerts an early protective effect by reducing bacterial load and likely toll-like receptor activation which in turn leads to a preserved β -arrestin 2 expression and a reduced HMGB-1 expression.